2005
DOI: 10.1007/s00383-005-1564-9
|View full text |Cite
|
Sign up to set email alerts
|

Further experience with OK-432 for lymphangiomas

Abstract: This study includes all the children treated with OK-432 for lymphangioma at our institute. Twenty-nine children treated between 1999 and 2003 are reported for the first time: twelve cases regressed completely, eight cases regressed more than 50% and seven remained unchanged; two cases were lost at follow-up. The outcome was related to the size of the cysts, the larger ones having a better prognosis. The adverse reactions are discussed and the methods of treatment are described in detail. Fifteen children, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
17

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 13 publications
(13 reference statements)
1
31
0
17
Order By: Relevance
“…Other treatment options including aspiration, drainage and irradiation give poor results [12,18,19,20]. Injection of OK-432 or marsupialization have also been advocated for unresectable cysts [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Other treatment options including aspiration, drainage and irradiation give poor results [12,18,19,20]. Injection of OK-432 or marsupialization have also been advocated for unresectable cysts [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…OK-432 is a sclerosing agent recently used in treating lymphatic vascular malformations. Its efficiency is well reported, especially in macrocystic lymphatic malformations, and even extensive lesions are effectively treated by injection of OK-432 [7,15,16]. Although the exact mechanism is not completely understood, the sclerosing effect of OK-432 seems to be related to its immunomodulatory activity and promotion of an inflammatory response followed by fibrosis and shrinkage of lymphatic tissue.…”
Section: E24mentioning
confidence: 92%
“…[4][5][6][7] This sclerosing treatment is much easier than surgery, leaves no scar, and carries no risk of causing nerve damage, and it should therefore be considered as the primary method of treatment for lymphangioma. 7 Recently, Taniguchi et al reported good results of 57 ganglia treated with OK-432 injection. 13 Pain and fever for several days were the only complications observed, and 56.6% of cases had complete cure.…”
Section: Case Reportmentioning
confidence: 99%
“…Injection of OK-432 causes the induction of infl ammatory cells, such as neutrophils, macrophages, and lymphokine activated killer cells, and probably induces a slow process of fi brosis. [4][5][6][7] We have successfully treated one large ganglion of the ankle with OK-432 injections.…”
Section: Introductionmentioning
confidence: 96%